Nutrition Knowledge Determinants among Undergraduate Students in Selected University in Jakarta - Dian Luthfiana Sufyan; Yuri Nurdiantami; Utami Wahyuningsih; Ade Fatma Krisdiani (Indonesian Journal of Human Nutrition, 2021)
Malnutrition problem (under and over nutrition), known as the double burden of malnutrition, was a growing concern in developing countries, including Indonesia. The 2018 Indonesia Basic Health Survey noted a substantial increase in the proportion of these nutritional impairments. As a fundamental factor of malnutrition, nutritional knowledge was expected to be occupied not only by vulnerable groups. A transitional age group like youth, in this case undergraduate students, should also be on the radar since they carried a risk of malnutrition from adolescence into adulthood. This study aimed to assess the nutritional knowledge determinants among undergraduate students in Jakarta. This cross-sectional study was conducted among undergraduate students in Universitas Pembangunan Nasional Veteran Jakarta. The nutritional knowledge regarding the Indonesian Guideline for Balance Diet, as well as participants’ characteristics questionnaire, was self-administered online by 235 participants using Google Form. Chi-Square, Spearman’s rho, and logistics regression tests were used to analyze the data using statistical software. Students who participated in this study were primarily female, aged under 20 years, achieve a GPA above 3.50, and had normal BMI. The bivariate analysis reported a significant association between sex, study field, and parent’s income with nutrition knowledge level. Based on logistic regression, the odds of having an adequate nutrition knowledge level is about 2.76 times higher among students whose parents earned 3-5 million IDR per month than students whose parents earned less than 3 million or more than 5 million IDR. Undergraduate students were also a prominent target group to ensure nutritional knowledge occupancy since they may face adolescent nutritional problems and future risk of adult nutritional problems. This study is fostering targeted nutrition education for youth undergraduate students.